I have the following factorial function

$(m-k-1)!(k-1)!$ for $m \in \mathbb{N}$, $m \geq 2$ and $k \in \{1,\cdots,m-1\}$.

I'm trying to find the value of $k$ for which the above expression attains minimum, or perhaps if there exists a function $f(m)$ such that

$f(m)! \leq (m-k-1)!(k-1)!$ for all $k \in \{1,\cdots,m-1\}$?

Plugging in certain values, it seems that the minimum is achieved for $k \approx m/2$, assuming $m$ is even. However, I have no idea about how to get the analytic expression.

Any help would be much appreciated. Thanks.

  • $\begingroup$ You might want to try taking derivatives of the gamma function. $\endgroup$ – abnry Sep 2 '13 at 2:54

You are looking for the lowest $k$ s.t. $(m-k-2)!k! \ge (m-k-1)!(k-1)!$

So we look for $k \ge m-k-1 \implies 2k \ge m-1$

Solving for the minimum $k_{min} =$ largest integer greater than or equal to $\dfrac{m-1}{2}$.

For odd $m$, this is $\dfrac{m-1}{2}$ and for even $m$, this is $\dfrac{m}{2}$

  • $\begingroup$ Hi Ross and Macavity, thanks both of you for your answers. Although they are correct, I'm afraid the proof might not be complete as all we have done is found a minimum. We'll have to additionally show that the function is convex so that any minimum is infact the global minimum. Have I got it correct? $\endgroup$ – Amit Sep 2 '13 at 4:29
  • $\begingroup$ @Amit factorial function is defined for natural numbers, so convexity is probably not the best way to go. $\dfrac{m-1}{k}-1$ is the ratio of preceding term to succeeding one, which decreases steadily with $k$. At some point it crosses $1$, which is our minimum. $\endgroup$ – Macavity Sep 2 '13 at 4:38
  • $\begingroup$ Yes, of course, thanks for this. I was trying to show convexity using the Gamma function as proposed by a previous post. Now everything is clear. Thank you a lot. $\endgroup$ – Amit Sep 2 '13 at 4:46

This method is not original by me.

Let $f(k) =(m-k-1)!(k-1)! $.

Then $r(k) =\dfrac{f(k+1)}{f(k)} =\dfrac{(m-(k+1)-1)!((k+1)-1)!}{(m-k-1)!(k-1)!} =\dfrac{(m-k-2)!k!}{(m-k-1)!(k-1)!} =\dfrac{k}{m-k-1} $.

If $k < m-k-1$ (i.e., $k < \frac{m-1}{2}$), $r(k) < 1$ so $f(k)$ is decreasing.

If $k > m-k-1$ (i.e., $k > \frac{m-1}{2}$), $r(k) > 1$ so $f(k)$ is increasing.

If $m$ is odd, then the minimum value is at $k=\frac{m-1}{2}$.

If $m$ is even, $r(\frac{m}{2}) =\frac{m/2}{m-m/2-1} =\frac{m/2}{m/2-1} >1 $ and $r(\frac{m}{2}-1) =\frac{m/2-1}{m-(m/2-1)-1} =\frac{(m-2)/2}{(m-2)/2} =1 $.

Therefore, if $m$ is even, the minimum value of $f(k)$ is at both $k=\frac{m}{2}$ and $k=\frac{m}{2}-1$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.